2017
DOI: 10.1016/j.ijimpeng.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface properties on momentum transfer to targets impacted by high-velocity sand slugs

Abstract: The response of dry and water saturated sand slugs impacting normally oriented and inclined rigid-stationary targets with four different surface coatings is measured with an emphasis on the quantification of the momentum transmitted from the slugs into the targets. The targets were coated with Alumina, PTFE, Aluminium or sandpaper layers in order to investigate the effect of varying surface hardness and surface roughness. In all the cases, the fraction of the slug momentum transferred into the target was equal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 38 publications
(84 reference statements)
4
15
0
Order By: Relevance
“…The sub-particles were assumed to be made from a solid of density ; = 2700 kg m oC (approximately equal to that of the quartz phase of silica) and the sub-particle contact model was defined by four parameters M , , O and ; . Liu et al 2013and Goel et al (2017) demonstrated that these parameters have a negligible effect on the interaction of the granular slug with the targets and thus following these studies we chose them to be M = 0.69 MN m op , O M ⁄ = 2 7 ⁄ (Bathurst and Rothenburg, 1988;Silbert et al, 2001), = 0.7 and ; = 0.6. The friction coefficient f between the particles and the target surface depends on the target surface and was varied over the range 0.0 ≤ f ≤ 2.0 in the calculations presented here.…”
Section: 4mentioning
confidence: 99%
See 4 more Smart Citations
“…The sub-particles were assumed to be made from a solid of density ; = 2700 kg m oC (approximately equal to that of the quartz phase of silica) and the sub-particle contact model was defined by four parameters M , , O and ; . Liu et al 2013and Goel et al (2017) demonstrated that these parameters have a negligible effect on the interaction of the granular slug with the targets and thus following these studies we chose them to be M = 0.69 MN m op , O M ⁄ = 2 7 ⁄ (Bathurst and Rothenburg, 1988;Silbert et al, 2001), = 0.7 and ; = 0.6. The friction coefficient f between the particles and the target surface depends on the target surface and was varied over the range 0.0 ≤ f ≤ 2.0 in the calculations presented here.…”
Section: 4mentioning
confidence: 99%
“…Since the objective is to investigate only the effect of grain shape, all the simulations were restricted to grains comprising either a single spherical particle or grains constructed by joining together sub-particles via rigid connections. A number of studies (Goel et al, 2017;Liu et al, 2013;Pingle et al, 2012) have shown that for slugs comprising spherical grains, the transmitted momentum normalised by the initial slug momentum 7 , is independent of the slug velocity 7 . Here, we confirmed via spot calculations that this result extrapolates to non-spherical rigid grains that do not fracture.…”
Section: Effect Of Particle Shapementioning
confidence: 99%
See 3 more Smart Citations